Development of Traffic Safety on Roads in The Progress of Electric Bicycle Technology in The Jurisdiction of The Bali Police - Putu Sekarwangi Saraswati (Faculty of Law, Universitas Pekalongan, 2025)
The widespread use of electric bicycles in Indonesia, which is starting to grow, hasgiven rise to pros and cons among the wider community. There are those who support it withthe aim of saving, but quite a few criticize it because it is used by more children and threatenssafety. Not to mention that there are a number of users who roam freely on the highway withoutpaying attention to a number of existing regulations. Progress in the transportation sector hasultimately encouraged developments in terms of legislation and transportation habits. The law isactually able to keep up with developments compared to the times. The current popularity ofelectric bicycles is progress in the field of transportation, but unfortunately this is not supportedby mature regulations. Although electric bicycles are very practical to use and make it easy for many peopleto ride them, even the elderly. It is also important to remember that electric bicycles are not yetincluded as the main mode of transportation and are registered in Indonesia because thecapacity of electric bicycles is limited and there are licensing issues. In this condition, theposition of electric bicycles can be said to face a legal vacuum as a result of things that are notregulated by law. There are no legal norms that specifically target vehicles with some criteriabeing motorized vehicles and others being non-motorized vehicles. Keywords: ElectricBicycle, Safety, Legal Vacuum, Legislation.